Feasibility studies of Biodistrict Establishment in Lankaran , Southern Azerbaijan a case study incorporating Agroecological Practices - Senghore, Ebrima (My University, 2026)
This paper evaluates the viability of developing a biodistrict in the Lankaran area of southern Azerbaijan based on agroecological activities, farmer willingness, institutional facilitation, and market environment. The mixed-method approach was employed, which included survey data of farmers, a case study of Citrus Valley Farm, and the opinions of policymakers related to the Ministry of Agriculture of Azerbaijan. The results from this study indicate that farmers in Lankaran region are already applying elements of agroecological practices, such as organic inputs, composting, and crop rotation, and show explicit willingness and readiness to transit and adopt sustainable agriculture farming. The specialization in citrus production and the favorable climate of the region also contribute to the potential of biodistricts. Nevertheless, the key issues are insufficient funding, poor institutional structures, and absence of certification systems, and poor consumer awareness of organic products in the area. Despite these challenges, both farmers and policymakers recognize and show interest in the potential of biodistricts to enhance sustainability, rural development, and market competitiveness. The research finds that biodistrict development in Lankaran is viable but needs specific policy support, capacity building and market development strategies to guarantee and facilitate successful implementation in the Lankran region.
Keywords: Biodistrict; Agroecology; Organic Farming; Sustainable Agriculture; Rural Development; Lankaran Region; Azerbaijan; Value Chains; Policy Framework; Agrotourism